The Thinkbox engagement study - Brennan, David (Henry Stewart Talks, 2009)
In-depth ethnographic study analyzing viewer behavior during TV commercial breaks |Understanding the roles of creative content, viewing context and audience attributes on advertising engagement, Evaluating the main drivers of audience engagement, Relating engagement to brand KPI's such as recall, awareness and intentions to purchase